Ultrathin Nanowires: Features of Transport in Ultrathin Gold Nanowire Structures (Small 6/2013). Issue 6 (15th March 2013) - Pud, Sergii; Kisner, Alexandre; Heggen, Marc; Belaineh, Dagmawi; Temirov, Ruslan; Simon, Ulrich; Offenhäusser, Andreas; Mourzina, Yulia; Vitusevich, Svetlana
<x xml:space="preserve">Abstract</x> The contact interface between large metal electrodes and ultrathin gold nanowires produced from a chemical synthesis is investigated by S. Pud, S. Vitusevich, and co‐workers. The conduction through this junction is influenced by physisorbed molecules on the nanowires. The electrical transport mechanism through the electrode–nanowires interface is explained on page 846 in the context of thermal fluctuationinduced tunneling theory, and is confirmed by microscopy measurements. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>